The Visual Complexity of Coronal Mass Ejections Follows the Solar Cycle. Issue 10 (5th October 2020) - Jones, S. R.; Scott, C. J.; Barnard, L. A.; Highfield, R.; Lintott, C. J.; Baeten, E.
Abstract: The Heliospheric Imagers on board National Aeronautics and Space Administration (NASA)'s twin STEREO spacecraft show that coronal mass ejections (CMEs) can be visually complex structures. To explore this complexity, we created a citizen science project with the U.K. Science Museum, in which participants were shown pairs of CME images and asked to decide which image in each pair appeared the most "complicated." A Bradley‐Terry model was then applied to these data to rank the CMEs by their "complicatedness, " or "visual complexity." This complexity ranking revealed that the annual average visual complexity values follow the solar activity cycle, with a higher level of complexity being observed at the peak of the cycle. The average complexity of CMEs observed by STEREO‐A was also found to be significantly higher than those observed by STEREO‐B. Visual complexity was found to be associated with CME size and brightness, but our results suggest that complexity may be influenced by the scale‐sizes of structure in the CMEs. Plain Language Summary: Coronal mass ejections (CMEs), or Solar Storms, are the main cause of hazardous space weather. Therefore, it is important we learn about their nature and evolution. Here we look at the visual complexity of CMEs in images from the Heliospheric Imagers (wide‐angle, visible‐light imagers) on board National Aeronautics and Space Administration (NASA)'s twin STEREO spacecraft. We created a citizen science project in collaboration with the UK Science Museum, where participants were shown pairs of CME images and asked to decide, which appeared to be the most complicated. We then ranked all the CMEs in order of perceived complicatedness, or complexity. This complexity ranking revealed that the annual average complexity values follow the solar activity cycle, meaning that the structure of the CMEs observed changes throughout the solar cycle. Key Points: A CME complexity ranking has been created by asking citizen scientists to compare CMEs in STEREO Heliospheric Imager observations The annual mean relative visual complexity values follow the solar cycle CMEs appear significantly more complex when observed by STEREO‐A than STEREO‐B